Less for More: The Structural Effects of Lean Manufacturing Practices on Sustainability of Manufacturing SMEs in Malaysia - Gusman Nawanir; Kong Teong Lim; Khai Loon Lee; Okfalisa Okfalisa; Taofeeq Durojaye Moshood; Ahmad Nur Aizat Ahmad (International Journal of Supply Chain Management, 2020)
As one of the important determinants of the health of the global economy, small and medium enterprises (SMEs) are responsible for several environmental degradations. The increase in resource consumption, climate change, biodiversity, water scarcity, and demographic changes and instability triggered society to consider sustainability issues. One of the operational initiatives related to sustainability is lean manufacturing (LM), which has become an imperative factor of organizational excellence in today’s volatile competitive market. However, it remains a critical question, does it positively affect corporate sustainability? This quantitative cross-sectional study examined the impact of LM on the triple bottom line (3BL) dimensions. A total of 159 manufacturing SMEs in Malaysia participated in this study. The analysis using the structural equation modeling (SEM) approach evidenced that the holistic implementation of LM practices contributes positively to all dimensions of 3BL. It implied that in order to enhance sustainability performance, SMEs should adopt the LM concepts holistically. This paper extends the boundary of knowledge by lessening the existing gaps in the literature to support the notion of potential implications LM on sustainability. Practitioners could grab benefits by understanding the critical initiatives and strategies towards the future sustainability of their businesses.